The rheumatoid arthritis and juvenile idiopathic arthritis associated major (A) allele of rs2104286 is a loss of expression variant of IL2RA. (22nd February 2011) - Clark, Joanna; Hinks, Anne; Eyre, Stephen; Thomson, Wendy; Cope, Andrew
Abstract : Background and objectives: The IL2RA /CD25 locus on chromosome 10p15 is emerging as a strong candidate susceptibility gene for the development of a range of autoimmune diseases, including rheumatoid arthritis, juvenile idiopathic arthritis, vitiligo, lupus, multiple sclerosis and type I diabetes. Variants that modify the function of the IL-2/IL-2R pathway are biologically highly plausible susceptibility variants, given recent data suggesting that IL-2 is a key cytokine involved in promoting peripheral tolerance through the generation and maintenance of regulatory T cell subsets, and suppressing expression of IL-17. While a number of allelic variants of IL2RA have been identified in fine mapping studies, the functional consequences of carrying a disease associated IL2RA variant are far from clear. In this study we evaluated the expression of IL-2Rα mRNA and protein in T cells from donors carrying the major and/or minor allele of the intron 1 rs2104286 single nucleotide polymorphism, since the major (A) allele has been shown to be associated with risk of developing rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA). Materials and methods: Fifty healthy donors were genotyped for expression of the protective (G) or risk (A) alleles of rs2104286. Expression of IL-2Rα mRNA in peripheral blood T cells was determined by RT-PCR and protein by flow cytometry, before or 4–24 h after stimulation with anti-CD3/CD28 beads. Results: We detected no differences in expression of IL-2Rα protein on resting peripheral blood T cells between GG, GA or AA donors. In contrast, activation induced expression of IL-2Rα was reduced in T cells from AA and AG donors, as compared to GG donors, 24 h after TCR stimulation. This was associated with a decrease in the percentage of CD25 hi but not CD25 int T cells derived from AA donors. A comparison of levels of mRNA expression in T cells from AA and GG donors after TCR stimulation revealed that donors carrying two copies of the protective G allele express higher levels of IL-2Rα mRNA than donors homozygote for the A risk allele. Conclusions: Our experiments indicate that susceptibility to JIA and RA, through carriage of the major A allele is associated with reduced expression of IL-2Rα mRNA and protein. This, RA and JIA associated IL2RA mutants are loss of expression variants.